Low rate of cardiovascular events in patients with acute myocarditis diagnosed by cardiovascular magnetic resonance - De Stefano, Luciano; de Arenaza, Diego Perez; Yeyati, Ezequiel Levy; Pietrani, Marcelo; Kohan, Andres; Falconi, Mariano; Benger, Juan; Dragonetti, Laura; Garcia-Monaco, Ricardo; Cagide, Arturo (Cardiovascular Diagnosis and Therapy, 2014)
Background: Myocarditis is a relatively common inflammatory disease that affects the myocardium. Infectious disease accounts for most of the cases either because of a direct viral infection or post-viral immune-mediated reaction. Cardiovascular magnetic resonance (CMR) has become an established non-invasive diagnosis tool for acute myocarditis. A recent large single centre study with patients with biopsy-proven viral myocarditis undergoing CMR scans found a high rate of mortality. The aim of this study was to assess the rate of clinical events in our population of patients with diagnosed myocarditis by CMR scan. Methods: Patients who consulted to the emergency department with diagnosis of myocarditis by CMR were retrospectively included in the study from January 2008 to May 2012. A CMR protocol was used in all patients, and were followed up to assess the rate of the composite endpoint of all-cause death, congestive heart failure, sudden cardiac death, hospitalization for cardiac cause, recurrent myocarditis or need of radiofrequency ablation or implantable cardiac defibrillator (ICD). A descriptive statistical analysis was performed. Results: Thirty-two patients with myocarditis were included in the study. The mean age was 42.6±21.2 years and 81.2% were male. In a mean follow up of 30.4±17.8 months, the rate of the composite endpoint of all-cause death, congestive heart failure, sudden cardiac death, hospitalization for cardiac cause, recurrent myocarditis or need of radiofrequency ablation or ICD was 15.6% (n=5). Two patients had heart failure (one of them underwent heart transplant), one patient needed ICD because of ventricular tachycardia and two other patients were re-hospitalized, for recurrent chest pain and for recurrent myocarditis respectively. Conclusions: In our series of acute myocarditis diagnosed by CMR we found a low rate of cardiovascular events without mortality. These findings might oppose data from recently published myocarditis trials.